Penurunan Residu Pestisida Pada Buah Dan Sayur Menggunakan Larutan Eco Enzyme Dan Sabun Produk Pabrik Z Tahun 2023 - Sri Ani; Agus Riyanto; Benedicta Tiara Nindiakristi (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Based on data from The Economics Intelligence Unit for 2021, Indonesia is the second largest producer of food waste in the world. Several innovations have sprung up to overcome this, one of which is Eco Enzyme, which is a multi-purpose liquid that can be used in everyday life such as mopping floors, cleaning dishes, washing fruits and vegetables, and others. Eco Enzyme is made from fruit peel waste, brown sugar and clean water. Based on the author's interest in using Eco Enzyme as a fruit and vegetable wash, research was carried out on the manufacture of Eco Enzyme and used as a fruit and vegetable wash and researched the reduction of pesticide residue levels in fruits and vegetables. This type of research is an experiment with a pretest and posttest group design. The population in this study were fruits and vegetables which were suspected of using pesticides from plantations in Kuningan Regency, West Java. Hence the research entitled "Reducing Pesticide Residues in Fruits and Vegetables Using Eco Enzyme Solutions and Factory Z Soaps in 2023". The results of the study based on testing the pesticide content in guava fruit before and after washing treatment using Eco Enzyme and Z soap were undetectable. For cabbage, the pesticide content was 0.009 mg/kg in the pre-treatment group and the average reduction after treatment with Eco Enzyme was 0.008 mg/kg while with Z soap, it was 0.005 mg/kg. Based on the results of the Paired T-Test, the reduction in pesticide content in cabbage obtained sig. (2-tailed) > 0.005, which means there is no significant difference in the reduction of pesticide content in fruits and vegetables before and after treatment using Eco Enzyme and Z soap.